2007
DOI: 10.1038/labinvest.3700545
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin activity negatively regulates bacteria-induced inflammation

Abstract: Wild-type (WT) Salmonella typhimurium causes acute intestinal inflammation by activating the nuclear factor kappa B (NF-kB) pathway. Interestingly, WT Salmonella infection also causes degradation of b-catenin, a regulator of cellular proliferation. Regulation of b-catenin and the inhibitor of NF-kB, IkBa, is strikingly similar, involving phosphorylation at identical sites, ubiquitination by the same E3 ligase, and subsequent proteasomal degradation. However, how b-catenin directly regulates the NF-kB pathway d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
177
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(187 citation statements)
references
References 26 publications
9
177
0
1
Order By: Relevance
“…Furthermore, XAV939 treatment or siRNA-mediated inhibition of β-catenin in infection led to an increase in NF-κB transcription and pro-inflammatory gene expression supporting a similar observation in other cell types. 21,34 Inhibition of β-catenin also resulted in increased host cell apoptosis with an overall decrease in parasite burden indicating its role downstream of AKT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, XAV939 treatment or siRNA-mediated inhibition of β-catenin in infection led to an increase in NF-κB transcription and pro-inflammatory gene expression supporting a similar observation in other cell types. 21,34 Inhibition of β-catenin also resulted in increased host cell apoptosis with an overall decrease in parasite burden indicating its role downstream of AKT.…”
Section: Discussionmentioning
confidence: 99%
“…20 β-catenin limits NF-κB mediated inflammatory responses in both Salmonella infection and TNF-α treatment by stabilizing Iκβ. 21 We, therefore, were interested to determine whether these two downstream effector molecules of AKT are modulated by infection. The present paper demonstrates a mechanistic insight into how by exploiting a single host protein AKT, Leishmania inhibits both proinflammatory response and host cell apoptosis by activating β-catenin through inhibition of GSK-3β on one hand and inactivating FOXO-1 on the other hand.…”
mentioning
confidence: 99%
“…Our study provides circumstantial evidence that in addition to the Wnt/␤-catenin pathway, Notch signaling is also activated during TMCH and may work in tandem with the Wnt/␤-catenin pathway to regulate hyperplasia and/or colitis following C. rodentium infection. We (23,24,28) and others (7,14) have shown that activation of the Wnt/␤-catenin pathway in the gut in response to bacterial infection is not unprecedented. However, neither the mechanism nor the consequence of aberrant regulation of the Notch pathway, either alone or in conjunction with Wnt/␤-catenin signaling, is clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…[181]. Another group of studies have shown that -catenin reduces Salmonella-induced inflammation in epithelial cells through an NFB-dependent mechanism [178] or a mechanism involving inhibition of GSK3mediated degradation [182]. On the other hand, -catenin is also associated with increased inflammatory cytokine production in various cell types.…”
Section: Does β-Catenin Interact With the Nfκb Pathway To Induce Pro-mentioning
confidence: 99%
“…In another study, LiCl treatment, which inhibits GSK3 activity and leads to β-catenin accumulation, resulted in reduction of Salmonella-induced IL-8 production. Moreover, cells expressing constitutively active -catenin had reduced NFB activity upon Salmonella infection [182].…”
Section: β-Catenin and Inflammationmentioning
confidence: 99%